2008
DOI: 10.1007/s10038-008-0343-6
|View full text |Cite
|
Sign up to set email alerts
|

PTPN11, SOS1, KRAS, and RAF1 gene analysis, and genotype–phenotype correlation in Korean patients with Noonan syndrome

Abstract: After 2006, germline mutations in the KRAS, SOS1, and RAF1 genes were reported to cause Noonan syndrome (NS), in addition to the PTPN11 gene, and now we can find the etiology of disease in approximately 60-70% of NS cases. The aim of this study was to assess the correlation between phenotype and genotype by molecular analysis of the PTPN11, SOS1, KRAS, and RAF1 genes in 59 Korean patients with NS. We found disease-causing mutations in 30 (50.8%) patients, which were located in the PTPN11 (27.1%), SOS1 (16.9%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 36 publications
8
79
2
4
Order By: Relevance
“…Different groups of clinicians reported a lower prevalence of short stature in patients with SOS1 mutations, compared with NS subjects harboring other genotypes [16][17][18][19]. In agreement, Malaquias et al, recently observed in 14 SOS1 patients a mean height SDS of +0.4 (±0.8) compared to NS standard (which is thus composed, in majority, of subjects mutated in PTPN11) [14].…”
Section: Influence Of Genotype On Spontaneous Growth In Subjects With Nssupporting
confidence: 60%
“…Different groups of clinicians reported a lower prevalence of short stature in patients with SOS1 mutations, compared with NS subjects harboring other genotypes [16][17][18][19]. In agreement, Malaquias et al, recently observed in 14 SOS1 patients a mean height SDS of +0.4 (±0.8) compared to NS standard (which is thus composed, in majority, of subjects mutated in PTPN11) [14].…”
Section: Influence Of Genotype On Spontaneous Growth In Subjects With Nssupporting
confidence: 60%
“…Indeed, the most frequent mutation found in NS is p .N308D (10,19). Mutation p.N308S has also been found in several studied patients (10,(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 87%
“…Whether the PTPN11 mutation or other mutations in the RAS-MAPK pathway are correlated with the growth response to rhGH treatment up to final height, merits further evaluation in larger prospective and representative studies [28,29]. Screening for mutations of the RAF1 and HRAS genes before rhGH therapy is important due to the development of progressive ventricular hypertrophy in NS children with RAF1 mutation [10,30] and the susceptibility to tumor growth in patients with Costello syndrome [31]. Recently, it has been reported that risk of cancer in patients carrying a mutation in PTPN11 is higher than the general population, particularly hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%